Exchange Market Reform, Inflation, and Fiscal Deficits - Ucer, E. (IMF Working Papers; Working Paper, 1995)
This paper examines the short- and long-run effects of exchange market reform in developing countries. The first part reviews the recent experience of Guyana, India, Jamaica, Kenya, Sierra Leone, and Sri Lanka with exchange market reform. The second part studies analytically the short-run dynamics of the parallel market premium and the money supply upon unification, when the post-reform regime consists of either a pure float or a managed float. The third part discusses the impact of unification on inflation and quasi-fiscal deficits, and identifies a variety of implicit taxes and subsidies that must be taken into account in assessing the longer-run effects of exchange market reform.